Clinical Outcome of Vitamin D Supplementation in Moderate and Severe COVID-19 Patients: A Randomized Clinical Trial (Academia Journal of Medicine, 2024)
The COVID-19 pandemic has posed a major global health challenge, especially for individuals with underlying health issues. This study aimed to assess the clinical outcomes of vitamin D supplementation in patients with moderate to severe COVID-19 in a tertiary care hospital through a randomized clinical trial. Sixty-two SARS-CoV-2 positive patients were enrolled and divided into intervention (vitamin D supplementation) and control groups.
Keywords: COVID-19; Vitamin D; Supplementation; Clinical Outcomes; Randomized Clinical Trial; Tertiary Care Hospital; Inflammatory Markers; Steroid-Sparing Effect